Noninvasive wearable sensor for indirect glucometry. Issue 18 (30th April 2018) - Zilberstein, Gleb; Zilberstein, Roman; Maor, Uriel; Righetti, Pier Giorgio
Abstract: A noninvasive mini‐sensor for blood glucose concentration assessment has been developed. The monitoring is performed by gently pressing a wrist or fingertip onto the chemochromic mixture coating a thin glass or polymer film positioned on the back panel of a smart watch with PPG/HRM (photoplethysmographic/heart rate monitoring sensor). The various chemochromic components measure the absolute values of the following metabolites present in the sweat: acetone, acetone beta‐hydroxybutirate, aceto acetate, water, carbon dioxide, lactate anion, pyruvic acid, Na and K salts. Taken together, all these parameters give information about blood glucose concentration, calculated via multivariate analysis based on neural network algorithms built into the sensor. The Clarke Error Grid shows an excellent correlation between data measured by the standard invasive glucose analyser and the present noninvasive sensor, with all points aligned along a 45‐degree diagonal and contained almost exclusively in sector A. Graphs measuring glucose levels five times a day (prior, during and after breakfast and prior, during and after lunch), for different individuals (males and females) show a good correlation between the two curves of conventional, invasive meters vs. the noninvasive sensor, with an error of ±15%. This novel, noninvasive sensor for indirect glucometry is fully miniaturized, easy to use and operate and could represent a valid alternative in clinical settings and for individual, personal users, to current, invasive tools.